Parent-Provider Communication and Antibiotic Prescribing for Pediatric Ear Infections. Issue 2 (15th March 2019) - Zhou, Yanmengqian; MacGeorge, Erina L.; Hackman, Nicole
Abstract : Rising rates of antibiotic-resistant infections make reducing unnecessary antibiotic use for outpatient illness a key public health issue. This study examines the association between parent-provider communication and rates of antibiotic prescribing for their children's ear infections. Participants (N = 70) were recruited from parents of patients (6 months–12 years) at a medical center whose children were diagnosed with ear infections or had ear symptoms with an upper respiratory tract diagnosis. Results showed that parent self-reports of going into great detail and asking many questions about their children's symptoms were associated with greater antibiotic prescribing, as was not insisting on a particular test or treatment. Further, antibiotic prescribing was less likely when parents reported that providers encouraged them to offer opinions about the child's medical treatment. Findings suggest that communication skills training is needed for both patients and providers to minimize potential misinterpretations and thereby avoid unnecessary antibiotic prescribing.